Challenges and Expectations of Online Arabic Language Teaching In The Covid-19 Pandemic Era - Mustapa, Al Muslim; Mohd Saad, Mohd Faizulamri; Abdul Ghani, Mohamad Zulkifli (Ijaz Arabi Journal of Arabic Learning, 2021)
The Covid-19 pandemic has changed the educational landscape around the world. In this era, higher education institutes offer fully online teaching and learning delivery as an alternative implementation. During the transition period, faculty and students experimented extensively to adapt to the new norms of education. This paper aims to reveal the positive academic experiences of Arabic language teachers during the past semester and their challenges. Belief in one's ability and readiness to face the coming day is essential for the following action plan by those in charge. It becomes an indicator for individuals to equip themselves and not be adequate with existing skills. Data were obtained through a questionnaire instrument to 12 respondents of Arabic language instructors and then analyzed based on the Fuzzy Delphi method. The study lists five (5) positive experiences and three (3) most fundamental challenges of online teaching. Belief in the readiness of implementing online teaching for the coming semester was also expressed. The actual situation of the teaching staff is an essential indicator in evaluating the effectiveness and quality of delivery during the Covid-19 pandemic. The educational landscape is far from changing and will never return to how it was before.